Prospective population‐based cohort of inflammatory bowel disease in the biologics era: Disease course and predictors of severity. Issue 9 (September 2015) - Niewiadomski, Olga; Studd, Corrie; Hair, Chris; Wilson, Jarrad; Ding, Nik S; Heerasing, Neel; Ting, Alvin; McNeill, John; Knight, Ross; Santamaria, John; Prewett, Emily; Dabkowski, Paul; et al.
Abstract Background and Aim We have previously found high incidence of inflammatory bowel disease (IBD) in Australia. A population‐based registry was established to assess disease severity, frequency of complications, and prognostic factors. Methods Incident cases were prospectively identified over 4 years. Early disease severity was assessed according to need for hospitalization and resective surgery and medication use. Results We report on the early outcomes (median 18 months, range 12–60 months) for 252 patients comprising 146 with Crohn's disease (CD), 96 with ulcerative colitis (UC), and 10 IBD undifferentiated. Eighty‐seven percent of CD patients had inflammatory disease at diagnosis, and this reduced to 73% at 5 years (n = 38). Immunomodulators were prescribed in 57% of CD patients and 19% with UC. A third of all CD patients were hospitalized, the majority (77%) in the first 12 months. Risk factors for hospitalization included penetrating, perianal, and ileocolonic disease (P < 0.05). Twenty‐four percent of UC patients were hospitalized, most within the first 12 months. Intestinal resection rates were 13% at 1 year in CD and 26% at 5 years. Risk factors include penetrating and stricturing disease (P < 0.001) and ileal involvement (P < 0.05). Colectomy rates in UC were 2% and 13% at 1 and 5 years. High C‐reactive protein (CRP) at diagnosis was associated with colectomy. Conclusions A high rate of inflammatory disease, frequent immunomodulator use in CD, and a low rate of surgery in both CD and UC were identified. In CD, ileal involvement and complex disease behavior are associated with a more severe disease course, while in UC a high CRP predicted this outcome.